2018
DOI: 10.1371/journal.pone.0205510
|View full text |Cite
|
Sign up to set email alerts
|

Variations in catastrophic health expenditure across the states of India: 2004 to 2014

Abstract: BackgroundFinancial protection is a key dimension of universal health coverage. Catastrophic health expenditure (CHE) has increased in India over time. The overall figures mask the subnational heterogeneity crucial for designing insurance coverage for 1.3 billion population across India. We estimated CHE in every state of India and the changes over a decade.MethodsWe used National Sample Survey data on health care utilisation in 2004 and 2014. The states were placed in four groups based on epidemiological tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 30 publications
6
43
2
Order By: Relevance
“…The reduction of CHE in Peru was similar to national estimates of a retrospective study worldwide [ 6 ], although it differs from the growing trend of CHE in countries in other parts of the world, such as Cambodia [ 32 ], Iran [ 33 ], India [ 34 ], or countries in the region, such as Brazil [ 35 ] and Chile [ 4 ]. Differences in population characteristics, poverty rates, national income level, economic structure, and payment mechanisms for access to health services may explain the difference in CHE proportions.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The reduction of CHE in Peru was similar to national estimates of a retrospective study worldwide [ 6 ], although it differs from the growing trend of CHE in countries in other parts of the world, such as Cambodia [ 32 ], Iran [ 33 ], India [ 34 ], or countries in the region, such as Brazil [ 35 ] and Chile [ 4 ]. Differences in population characteristics, poverty rates, national income level, economic structure, and payment mechanisms for access to health services may explain the difference in CHE proportions.…”
Section: Discussionsupporting
confidence: 65%
“…One study found that 12.9% of Peruvians reported that they did not receive medical care because they did not have money, and 43.1% of people in moderate or extreme poverty claimed that money was a barrier for access to healthcare [31]. The reduction of CHE in Peru was similar to national estimates of a retrospective study worldwide [6], although it differs from the growing trend of CHE in countries in other parts of the world, such as Cambodia [32], Iran [33], India [34], or countries in the region, such as Brazil [35] and Chile [4]. Differences in population characteristics, poverty rates, national income level, economic structure, and payment mechanisms for access to health services may explain the difference in CHE proportions.…”
Section: Discussionmentioning
confidence: 77%
“…Alarmingly poor availability in government hospitals drives patients to OOP payments in GSDPs or private retail pharmacies. Pandey et al [36] reported that Kerala has the highest burden of catastrophic health expenditure in India, where over 43% households spend ≥10% of total household expenditure on healthdisproportionately affecting the poor. Therefore, government must allocate adequate funds, and streamline medicine procurement and supply systems to ensure a steady supply of medicines, either free or at affordable prices, in public sector facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Given the chronic nature of disease, affordability should be seen in context of lifelong polypharmacy [46]. For instance, coronary heart disease would require daily therapy with aspirin, statins, beta-blockers and ACE-inhibitors [35][36][37][38], the monthly supply of which would cost about 2.9-10.3 days' wages, depending on the medicines prescribed. In diabetes, monotherapy with glimepiridefirst line medicine along with metforminas well as insulin are unaffordable in Kerala.…”
Section: Discussionmentioning
confidence: 99%
“…In reverse, being in speci c social, cultural, and economic conditions can enhance the risk of disability (18,19). Farrowing growth in socio-economic inequality aggravates the risk of an increase in the unmet need for healthcare in developing countries (20).…”
mentioning
confidence: 99%